Length–weight relations of 15 deep-sea fish species (Actinopterygii) from the north-western African continental slope - C. Meiners-Mandujano; L. Fernández-Peralta; A. Faraj; R. García-Cancela (Acta Ichthyologica et Piscatoria, 2018)
Length–weight relations (LWR) of 15 teleost fish species from deep waters off the NW African coast were estimated. In total, 4045 specimens, representing 12 families and 15 species, were caught and studied. The following species were covered: Alepocephalus bairdii Goode et Bean, 1879; Beryx decadactylus Cuvier, 1829; Beryx splendens Lowe, 1834; Schedophilus ovalis (Cuvier, 1833); Diretmichthys parini (Post et Quéro, 1981); Micromesistius poutassou (Risso, 1827); Lophius vaillanti Regan, 1903; Mora moro (Risso, 1810); Scorpaena elongata Cadenat, 1943; Trachyscorpia echinata (Köhler, 1896); Helicolenus dactylopterus (Delaroche, 1809); Gephyroberyx darwinii (Johnson, 1866); Aphanopus carbo Lowe, 1839; Zenopsis conchifer (Lowe, 1852); Zeus faber Linnaeus, 1758. The values of the parameter b remained mostly within the expected range of 2.5–3.5. This study provides the first published LWR for five fish species, contributing to the first four references on the LWR for this area. It also presents new maximum lengths for two fish species.